(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
This study reveals the extent to which PhD students of pedagogy in Hungary are aware of the applicability of Computer Assisted Qualitative Data Analysis, focusing on MAXQDA and it also points out the frequency of its use in their practice. Results were gained by means of structured interviews and their coding was based on deductive and inductive logics. 109 coded units and 34 different codes led to the exploration of the strong points and difficulties of MAXQDA and Computer Assisted Qualitative Data Analysis and the illustration of those pedagogical research areas in which students claimed their use to be relevant.